The effect of preventive exercises on the range of motion of the ankle joint For young soccer players (Journal of the College of Basic Education, 2023)
Summary of the research:The aim of the research is to prepare preventive exercises to develop the range of motion of the ankle joint, which are suitable for the research sample. To learn about its effect on the prevention of injury to the ligaments of the ankle joint and its effect on the variable flexibility of young soccer players. The researchers used the experimental approach in the design of one group due to its suitability to the nature of the research, and the research community was determined by young soccer players in specialized schools in Baghdad for the year (2021-2022), which numbered (35) players, then the sample was chosen by the intentional method from the original community by (10). players, and the duration of the preventive program lasted three months at the rate of three units per week, as the total number of units of the preventive program was (36) units, and after the completion of the program, post-tests were conducted. The appropriate statistical treatments were used to reach a number of results, the most important of which is that there are significant differences between the pre and post tests for one group in favor of the post tests. The most important of which was the adoption of the preventive program that was prepared in the current research after its approval in the training of football players by the competent authorities in this field.Keywords: preventive exercises - range of motion - ankle joint - soccer.